Development of heterogeneous catalyst from assorted periwinkle snail shells for sustainable biodiesel synthesis - Ogunkunle Oyetola; Laseinde Opeyeolu Timothy (E3S Web of Conferences, 2023)
Owing to the environmental friendliness of biodiesel compared to fossil fuels, its application in internal combustion engines has gained wide recognition. The biodiesel industry requires effective heterogeneous catalysts developed from agricultural biomass/residues due to their overall cost-effectiveness, recoverability, and reusability. Scientific reports on developing active heterogeneous catalysts from periwinkle snail shells for application in transesterification reactions are limited, as there is no evidence of stability test results for the catalyst’s structural and elemental composition analysis. Also, there is a deficit of information on the catalytic effect on biodiesel yields. This research developed a heterogeneous catalyst derived from periwinkle snail shells (PSS) for biodiesel production. Pulverized PSS were sieved through several apertures to separate the samples into different particle sizes, viz. 250 mm, 500mm, and 1000 mm. The samples were calcined in an electric furnace at 500 oC for 3 and 5 hrs. The calcined catalyst samples were characterized using XRD, SEM, and EDS. Purified WCO was transesterified using the CPSS with the highest metallic oxides percentage under different experimental levels. All the CPSS samples exhibited a change in colour and weight loss after the calcination period. XRD observations revealed that calcium oxide (CaO) is the principal constituent of the calcined PSS (CPSS). The results showed that the highest (93%) traces of CaO was found in PSS 500 mm size calcined at 500 oC for 5 hrs. EDS results showed that the same sample had the highest calcium (Ca) composition with a weight percent of 57.38%. The highest biodiesel yield of 94.6% was obtained at optimum conditions of 70 oC reaction temperature, 9:1 molar ratio, 60 minutes reaction period, and catalyst content of 3 wt%. It was observed that biodiesel yields decreased when the catalyst concentration increased beyond 3wt%. Compared to the same amount of homogeneous catalyst, KOH, an average biodiesel yield of 90% was recorded from the same transesterification reaction conditions. The development of heterogeneous catalysts from PSS was established as a cost-effective means of catalyzing transesterification reactions and obtaining high biodiesel yields from WCO with the prospects of possible catalyst recovery and reuse.